Effects of fertilizers on the traits of Aloe vera Plants infected with fungus Rhizoctonia solani - Mazin Badri AL-Ethawi; Huda Hazim AL-Taae (Zien Journals, 2022)
This study was conducted in a greenhouse at the Plant Protection Department, Agriculture and Forestry College, Mosul University, Mosul, Iraq, to study the causative pathogen for root and stem-end rot of Aloe vera plants. In addition to examining the effectiveness of various types of fertilizers in preventing aloe vera plants from becoming infected with pathogenic fungus, this paper will also study their capacity to enhance the plant's development features . The isolation and diagnosis results revealed the related fungal species Rhizoctonia solani, Fusarium solani, Alternaria alternata, Cliendero carbon spp, Fusarium oxspurium, Aspergalus flaves, Aspergalus negir, and Pincillum spp to the aloe vera plant, where Rhizoctonia solani took the lead, which is the most frequent fungus
Keywords: Aspergalus; Pincillum; vera; Rhizoctonia